Collaboration and disaster: critical responses after tsunami events in Indonesia. (8th August 2021) - Warganegara, Arizka; Samson, Maxim G. M.
ABSTRACT: Lampung, located in the southern part of Sumatra, is an example of a disaster-prone province in Indonesia. South Lampung regency in particular is at potential risk of three natural disasters: tsunamis, earthquakes and volcanic eruptions. Through drawing upon interviews with authority figures from two districts of the regency (Kalianda and Rajabasa) and applying the collaborative governance theory of Ansell and Gash, this article contributes in two important ways to the literature on post-tsunami response. First, we identify the role played by three groups – local government, adat and religious institutions – in negotiating the post-tsunami response process, alongside the socio-technical issues encountered. Second, through applying and refining the ideas of Ansell and Gash, we create a model that may be used to stimulate collaboration between the three groups to better deal with tsunami events. It is evident that when local government lacks the capability to coordinate post-tsunami response, disaster management may easily descend into chaos. By identifying the resources each group brings to the table, we believe that our model can help encourage different actors to collaborate when responding to such disasters.